The Scavenger Women’s Strategy in Fulfilling Family Economy in Makassar City : Case of scavengers involving Toddlers in Urban Areas - Ikhsan, Nur; Fachry, Mardiana Ethrawaty; Radjab, Mansyur (Jurnal Perempuan dan Anak, 2024)
Poverty is still a problem in urban areas. Limited skills and employment have caused women from poor families to also seek work as scavengers or collectors of waste and used goods to help support their family's economy. This study aims to find the characteristics of female scavengers in responding to the phenomenon of poor women in fulfilling their family's economy. The involvement of children under five in the scavenging process is also a review in finding the distribution of gender roles in scavenger households. This research was conducted in Makassar City using a qualitative approach. Data was obtained from 25 families of female scavengers. The results of the study found that female scavengers aged between 23 and 45 years with an education level of not having finished elementary school were 20%. graduated from elementary school 72% and junior high school 8%. Age of family between 4 to 18 years, with an average dependent of 3 children. In scavenging activities involving children aged between 1 and 5 years which is a domestic role and a strategy to get additional income from the compassion of the community. The average income of a scavenger family is between Rp. 1,200.00 to Rp. 2,050,000. Family expenses consist of basic needs in the form of consumption 28.5%, needs for children under five 24.4% and paying debts 13.3%. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation, which has not yet become the attention of the Makassar city government. In scavenging activities involving children aged between 1 and 5 years which is a domestic role and a strategy to get additional income from the compassion of the community. The average income of a scavenger family is between Rp. 1,200.00 to Rp. 2,050,000. Family expenses consist of basic needs in the form of consumption 28.5%, needs for children under five 24.4% and paying debts 13.3%. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation, which has not yet become the attention of the Makassar city government. In scavenging activities involving children aged between 1 and 5 years which is a domestic role and a strategy to get additional income from the compassion of the community. The average income of a scavenger family is between Rp. 1,200.00 to Rp. 2,050,000. Family expenses consist of basic needs in the form of consumption 28.5%, needs for children under five 24.4% and paying debts 13.3%. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation, which has not yet become the attention of the Makassar city government. Family expenses consist of basic needs in the form of consumption 28.5%, needs for children under five 24.4% and paying debts 13.3%. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation, which has not yet become the attention of the Makassar city government. Family expenses consist of basic needs in the form of consumption 28.5%, needs for children under five 24.4% and paying debts 13.3%. Scavenger women make an economic contribution to the family between 40% and 77%. The involvement of children under five in the scavenging process is a form of child exploitation, which has not yet become the attention of the Makassar city government.